Analisis Pengaruh BMI, Tinggi Rak dan Berat Barang Terhadap Energy Expenditure Pekerja Bagian Manual Material Handling - Oktiarso, Teguh; Safitri, Safitri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The present study aims to determine the effect of BMI, shelf height, and weight of goods on energy requirements in manual material handling (MMH) activities. The BMI levels considered are thin and normal, while the weight of goods is classified into two levels, 5 kg and 10 kg. The shelf height is also classified into two levels, 76 cm and 126 cm. The research respondents were four male workers aged 18-25 years. The results of the ANOVA test demonstrate that the three factors have an influence on energy requirements, as well as the interaction between BMI and weight of goods on energy requirements. The results of further tests using the Duncan test show that respondents with a thin BMI required more energy than respondents with a normal BMI when lifting 10 kg. Conversely, the disparity in energy requirements between lean and normal BMI respondents when lifting 5 kg was not significant. The findings of the energy consumption calculation indicate that the energy required by workers to perform MMH activities in this study falls within the light workload criteria.